Phylogeny of the planthopper genus Megamelus (Hemiptera, Delphacidae), with the description of two new species from South America - Nicolas A. Salinas; Roxana Mariani; Ana M. Marino de Remes Lenicov; Marcela S. Rodriguero; Alejandro J. Sosa (ZooKeys)
Megamelus is a genus of Delphacidae widely distributed and mostly associated with plants in freshwater environments. Despite various taxonomic revisions and thorough research, the delimitation of the genus, its diversity, and its evolutionary history need to be further explored. Moreover, features originally considered distinctive of the genus exhibit variation and should be reassessed. Here, the genus Megamelus in South America was examined, describing two new species, Megamelus delticus Remes Lenicov & Mariani, sp. nov. and Megamelus serpentinus Mariani & Remes Lenicov, sp. nov., and providing information on their host plants and geographical distribution. The distribution and host range knowledge of Megamelus iphigeniae and Megamelus timehri are also expanded, the male brachypter of M. timehri described for the first time, and a key to distinguish the species, based on male and female genitalia and their external morphology, is provided. Moreover, the first phylogenetic analysis of the genus is presented, based on the mitochondrial COI gene to clarify the interspecific relationships among its members. Our combined findings support the monophyly of the genus and refine diagnostic features, including the importance of the pygofer’s lobed appearance. This comprehensive revision highlights the need for further multidisciplinary approaches to fully understand the evolutionary history of Megamelus and its interactions with host plants and environments.